Maintenance Of Winchlass Hydraulic Oil Pump In Supporting Mooring Un Mooring In Kl Sultan Hasanuddin 02 - Suyuti, Suyuti; Jamaluddin; Musriady; Muh Jafar (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
Windlass machine is a tool on a ship that is used to pull and lower anchors and is usually also used to moor ropes when the ship is docked at the dock. In its operation, this windlass machine consists of an anchor, anchor chain, windlass, hydraulic pump, electric motor. The hydraulic pump functions to convert mechanical energy into hydraulic energy by pressing the hydraulic fluid in the system to drive the main shaft of the anchor machine, to make it easier for the crew to lego and hibob anchors. If in a less than optimal condition, it will disrupt the performance of the windlass and cause damage and shorten the service life. This happens because there is no maintenance and repair to avoid damage, especially to the hydraulic pump. This study aims to ensure that the performance of the windlass in its supervision and operation remains optimal in ship service.